2022
DOI: 10.1002/ijc.34005
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sex hormones, aromatase activity and lung cancer risk in postmenopausal never‐smoking women

Abstract: Although reproductive factors have been repeatedly associated with lung cancer risk, no study to date has directly evaluated the relationship with endogenous sex hormones nor with aromatase activity in postmenopausal never-smoking women. A case-control study of 397 incident lung cancer cases and their individually matched controls, nested within the Shanghai Women's Health Study, was conducted among postmenopausal women who were lifetime never smokers. Prediagnostic concentrations of sex hormones was quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…The distinct patterns of testosterone and androgen receptor expression patterns observed in the thyroid tissues of men and women could contribute to the gender-specific incidence of thyroid tumors [ 28 ]. In a case–control study, high levels of circulating free testosterone were negatively associated with the risk of lung cancer in postmenopausal never-smoking women [ 29 ].Nevertheless, our findings indicated a negative correlation between women's testosterone levels and the risk of ovarian and thyroid cancers. A previous extensive prospective, nested case–control study suggested no clear causal relationship between testosterone and ovarian cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct patterns of testosterone and androgen receptor expression patterns observed in the thyroid tissues of men and women could contribute to the gender-specific incidence of thyroid tumors [ 28 ]. In a case–control study, high levels of circulating free testosterone were negatively associated with the risk of lung cancer in postmenopausal never-smoking women [ 29 ].Nevertheless, our findings indicated a negative correlation between women's testosterone levels and the risk of ovarian and thyroid cancers. A previous extensive prospective, nested case–control study suggested no clear causal relationship between testosterone and ovarian cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether testosterone levels are a risk factor or predictor of prostate cancer prognosis remains unclear. A case–control study suggested that high levels of circulating free testosterone may be associated with a reduced risk of lung cancer in postmenopausal never-smoking women [ 6 ]. Another study suggested that premenopausal women with elevated serum testosterone levels have an increased risk of breast cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%